The Role of Social User and Social Feature on Recommendation Acceptance in Instagram in Indonesia - Muhammad Aldi Yusron; Putu Wuri Handayani; Qorib Munajat (IAES Indonesia Section, 2018)
This study aims to identify the effect of social features and social users on recommendations acceptance on shopping activities in Instagram. This study uses quantitative approach to process 654 data collected using online questionnaire. The data were analyzed using CB-SEM method and AMOS 21 tools. The results of this study showed that social features and social users give moderating effect on the relationship between social recommendation, cognitive appraisal and affective appraisal. Meanwhile, affective and cognitive appraisal was found to affect purchase intention. The finding shows that the user giving recommendation and the features used to make recommendation can influence the level of recommendation acceptance.